Mobile Technologies for Delivering Healthcare in Remote, Rural or Developing Regions - Ray, Pradeep; Nakashima, Naoki; Ahmed, Ashir; Soshino, Yasuhiro; Ro, Soong-Chul (Associate professor) (The Institution of Engineering and Technology, 2020)
This edited book explores the use of mobile technologies such as phones, drones, robots, Apps, and wearable monitoring devices for improving access to healthcare for socially disadvantaged populations in remote, rural or developing regions
Keywords: Automation -- Human factors.; Clinical medicine -- Computer programs.; Design -- Human factors.; Medicine -- Data processing.; Mobile robots.; Sustainable development.; Medical informatics.; elektronické knihy; electronic books